PELATIHAN MEMBUAT MEDIA TANAM (BAGLOG) BUDIDAYA JAMUR TIRAM BAGI WARGA RT.001/RW.011 KELURAHAN LANGKAI KOTA PALANGKA RAYA Training of Making Plant Media (Baglog) Oyster Mushroom for Residents of RT.001 / RT.011 Langkai Village Pahandut District of Palangk: Novalisae1), Prihanika1) , Devia2) (Agrienvi: Jurnal Ilmu Pertanian, 2020)
Raya City about making good quality and inexpensive baglog (planting media) for oyster mushroomcultivation, the team sought help by bringing in one of the Oyster Mushroom Cultivation Producers that can beused Optimal named Mr. Budi who has a scale of oyster mushroom cultivation business located at Jl. MurjaniGang Suka Damai, Palangka Raya City. He and the research team will provide training on oyster mushroomcultivation to residents of RT.001 / RW.011 Langkai Village, Pahandut District, Palangka Raya City. Thesolution offered is assistance for residents of RT.001 / RW 011 is to provide insight and knowledge on theimportance of making the correct mushroom growing media (baglog) in order to produce oyster mushroomswith optimal results so that it does not experience failure, namely providing training on oyster mushroomcultivation with resource persons an oyster mushroom cultivator who works in the city of Palangka Rayanamed Mr. Budi. Training in the form of the introduction of tools and materials needed for the manufacture ofoyster mushroom growing media, mixing materials for growing media, baglog packing, baglog sterilization,inoculation process (administration of mushroom seeds), incubation (mushroom growth), harvesting andprocessing of oyster mushrooms in the form of crispy mushrooms.Keywords: Training, Cultivation, Making Media Planting (Baglog), Oyster Mushroom.